Horizontal and vertical heterogeneity of sediment microbial community in Site F cold seep, the South China Sea - Zhai, Xinyi; Shi, Xiaochong; Cheng, Haojin; Yao, Peng; Zhao, Bin; Chen, Lin; Liu, Jiwen; Cao, Lei; Wang, Minxiao; Fu, Lulu; Zhang, Xiao-Hua; Yu, Min (Frontiers in Marine Science, 2022)
Site F is the most vigorous cold seep known on the continental slope of the northern South China Sea. Up to now, the microbial community structures in sediments of Site F based on the high-throughput sequencing of the 16S rRNA genes have been studied extensively. However, few studies investigated the microbial community structures at fine vertical scales of Site F and control stations outside Site F. In this study, a comprehensive investigation of microbial communities in sediments of Site F along the depths varying from 0 to 24 cm below sea floor (cmbsf) of four sampling sites—SRS (Southern Reduced Sediment), NRS (Northern Reduced Sediment), Control 1 (close to Site F), and Control 2 (far from Site F)—was carried out. The high relative abundances of anaerobic methanotrophic archaea (ANME), Desulfobacterota [sulfate-reducing bacteria (SRB)], and Campylobacteria [sulfur-oxidizing bacteria (SOB)] in SRS and NRS indicated that these two sites were newborn cold seep sites compared with non-seep sites, Control 1, and Control 2. A positive correlation between ANME-1b, ANME-2, and SEEP-SRB and an enrichment of Sulfurovum and Methlomonadaceae were found in the surface sediments of both SRS and NRS, indicating that the processes of anaerobic oxidation of methane (AOM), sulfur oxidation, and sulfate reduction might occur in seep sites. SRS was enriched with ANME-1b and SEEP-SRB2 with a proposed sulfate-methane transition zone (SMTZ) approximately located at 8 cmbsf. The high abundance of ANME in SRS may due to the high concentration of methane. NRS was enriched with ANME-2, Desulfatiglans, Sulfurovum, and Methanosarcinaceae with a proposed SMTZ at about 10 cmbsf. According to the analyses of microbial community structure and environmental factors, NRS could be described as a notable cold seep reduced sediment site with low sulfate and high H2S that nourished abundant SEEP-SRB1, ANME-2, Methanosarcinales, and Sulfurovum, which showed similar distribution pattern. Our study expands the current knowledge on the differences of microbial communities in cold seep sites and non-seep sites and sheds light on the horizontal and vertical heterogeneity of sediment microbial community in Site F.